(untitled) (Karya Ilmiah Mahasiswa (KIMA), 2023)
This research aims to determine the effectiveness of using culturally oriented materials in reading comprehension and to determine students’ achievement of literal reading comprehension through culturally oriented materials. This research used quantitative methods with pre-experimental research using pre-test and post-test. The population in this research were all students of class X SMAN 1 Polewali with a total of 385 people. While the sample of this research was taken as many as 35 students. The instrument used in obtaining data is to provide text, namely the pretest, and posttest. This research was conducted over six meetings to improve students’ reading comprehension at SMAN 1 Polewali. The data were analyzed based on SPSS 25. From the results of this research, the average post-test was higher than the pre-test 59.83 < 79.58. Proving that using culture-oriented materials is effective in improving reading ability, the percentage of post-test results is higher than the percentage of pre-test results. The results of the t-test = (-13.988) with a df of 34 and a significance of 0.000. Percentage increase obtained 33%. While the results of the questionnaire show that all of the seven research questions prove that culturally oriented reading comprehension is easy to understand and obtains a lot of information by knowing something new by reading culturally oriented material. This research proves that the use of culturally oriented materials in teaching and learning English is attractive to students and can improve their reading comprehension skills. The results of the research found a significant difference between the pretest and posttest scores, which proves that the use of culturally oriented materials has a positive impact on student learning outcomes. This research also found that reading culturally oriented material can motivate students to be more interested in increasing their interest in reading.